2018
DOI: 10.3390/ani8050074
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment in the Sucker and Weaner Phase Altered the Performance of Pigs in Three Behavioural Tests

Abstract: Simple SummaryTwo important questions about the intensive housing of pigs concern whether young pigs require environmental enrichment to enhance their welfare, and from what age should enrichment be provided to pigs to achieve the benefit? We provided sucker and weaner pigs with enrichment in the form of blocks, which they could push around the floor of the pen, compared to no blocks (‘barren’ control). Behavioural and physiological responses of the pigs were then measured in a series of standard tests used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There was no difference between treatments, although the cortisol level increased after transfer from the farrowing pen to the nursery pen. We hypothesized that algae cylinders, as a better source of stimulation than other material, would prepare the animals to cope with new stressing challenges (separation from the sow and changes in diet and environment) and to adapt faster to new situations, as suggested in other experiments [ 12 , 13 , 34 ]. The results tend to demonstrate that, in farrowing pens, the algae objects were not sufficient for piglets to enhance their ability to cope with a new situation.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between treatments, although the cortisol level increased after transfer from the farrowing pen to the nursery pen. We hypothesized that algae cylinders, as a better source of stimulation than other material, would prepare the animals to cope with new stressing challenges (separation from the sow and changes in diet and environment) and to adapt faster to new situations, as suggested in other experiments [ 12 , 13 , 34 ]. The results tend to demonstrate that, in farrowing pens, the algae objects were not sufficient for piglets to enhance their ability to cope with a new situation.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four studies (50.7%) did only perform an OF test whereas another 35 studies additionally used NOT and/or HAT (Figure Figure 6: Duration pigs spent in a start box, in the Open Field with additional NOT or HAT.). In six studies (8.7%) a start box with an initial waiting and acclimatization time was used with a mean of 2.14min ± 1.87 [53,62,63,68,71,77]. In the majority of studies, the OF behavioral test lasted for 10 min (8.92 min ±12.2).…”
Section: Size Of Openmentioning
confidence: 99%
“…In addition to the field dimensions, other parameters may also have an impact on the behaviour of pigs during the OFT. Ralph et al [ 13 ] noted that pen enrichment during the sucking and weaner phases alters the performance of piglets. Later, Tatemoto [ 14 ] additionally demonstrated that maternal behaviour influences the piglets' behaviour via foetal reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Forkman et al [ 18 ] also investigated the repeatability of this test, demonstrating heterogeneous results encompassing no [ 19 ] to positive repeatability [ 20 ]. Several factors are known to also influence the NOT, such as enrichment in the home pen [ 13 , 21 ], an individual's character [ 15 ] or epigenetic characteristics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%